To the design of highly fracture-resistant composites by the application of the yield stress inhomogeneity effect. (1st February 2018) - Sistaninia, M.; Kasberger, R.; Kolednik, O.
Abstract: Improvement of the fracture toughness by the introduction of thin, soft interlayers is investigated. The mechanism is the strong decrease of the crack driving force when the crack tip is located in the soft region. Based on numerical simulations with the configurational forces concept, it is demonstrated that the fracture toughness of brittle materials can be greatly improved by the introduction of soft interlayers, if the architectural parameters of the multilayer are appropriately chosen. The findings are compared to experimental results of fracture tests conducted on compounds made of high-strength steel as matrix and low-strength steel as interlayer material. The design concept presented in this paper can be applied for various types of composite materials.